The Extraordinary Imperial Ambassadors to the Conclave during the 1667–1730 Period - Jiří M. Havlík (Theatrum Historiae)
This study focuses on the practice of the appointing of extaordinary imperial ambassadors and representatives for papal elections during the years 1667–1730. To describe the development and the changes in the approach to this issue during the period monitored the author selected three model cases – the last mission of Cardinal Ernst Adalbert von Harrach at a conclave in 1667, the appointing of the extraordinary secular ambassador to the conclave, Anton Florian von Lichtenstein, in 1689 and the mission of Antonio Rambaldo di Collalto who, in 1730, collaborated with the ordinary Imperial Resident, Cardinal Cienfuegos. The study is based on the family archives of Harrach (held in the Österreichisches Staatsarchiv in Vienna), and of Collalto and Kaunitz (both are held in the Moravský zemský archiv in Brno) and on the diplomatic correspondence and the recorded agenda of the Imperial Embassy in Rome that is preserved in the Haus-, Hof- und Staatsarchiv in Vienna. The period in question can be divided into three different sections. For the papal elections in 1667, 1669 and 1676 Emperor Leopold I appointed those cardinals who favoured the House of Habsburg. After the death of Pope Innocent XI in 1689 the situation changed to the detriment of the Habsburg dynasty and Leopold I decided to appoint an extraordinary secular ambassador. Anton Florian von Liechtenstein, in cooperation with Cardinal Johann von Goess, was supposed to correct the steps of the not so reliable Cardinal Protector Germaniae et Hispaniae Francesco Maria de’Medici. Liechtenstein’s task was to build-up prestige and to establish a permanent embassy at the Holy See. During the years 1691–1730 the practice of appointing extraordinary secular ambassadors to the conclave had already stabilised – mostly they were imperial counts who intervened with total respect in the events that took place around the papal election.